A predictive model for the utilization of curative ambulatory health services in Mexico Un modelo predictivo de la utilización de servicios de salud ambulatorios curativos en México - Atanacio Valencia-Mendoza; Stefano M Bertozzi (Instituto Nacional de Salud Pública, 2008)
OBJECTIVES: To estimate the degree to which individual and household variables jointly predict utilization of curative ambulatory services in Mexico for four types of health providers. MATERIAL AND METHODS: Patient choice of provider (self-care, Ministry of Health, social security, or private provider) when they become ill is modeled using a nested multinomial logit model that uses household and individual variables as predictors. The data are from the Mexican National Health Survey conducted in 2000. RESULTS: Being a social security beneficiary is one of the most important predictors of utilization. A strong positive relationship between socio-economic status (SES) and demand for services was also found, with the strongest relationship being for private providers, followed by social security. Utilization of Ministry of Health (MoH) services was negatively associated with household SES. CONCLUSIONS: Expansion of health insurance coverage should significantly reduce health inequalities due to reduced care-seeking by non-beneficiaries. OBJETIVO: Estimar el grado en el cual variables individuales, del hogar y comunitarias predicen la utilización de servicios ambulatorios curativos en México. MATERIAL Y MÉTODOS: Ante un problema de salud los individuos pueden elegir utilizar servicios médicos, servicios de la Secretaría de Salud (SSa), de la Seguridad Social (SS) o Privados (SP). Esta elección es modelada con datos de la ENSA 2000 mediante un modelo logístico multinomial anidado. RESULTADOS: El predictor más importante de la utilización de servicios de salud fue la derechohabiencia a la SS. Se encontró una fuerte relación positiva entre estatus socioeconómico (ESE) y la utilización de servicios de salud. Dicha relación es mayor para la utilización de SP, seguida de la SS. Se encontró una relación negativa entre el ESE y la utilización de servicios de la SSa. CONCLUSIÓN: Expandir la cobertura de aseguramiento reduciría significativamente las inequidades en salud debidas a la baja utilización de servicios de salud por los no beneficiarios.